POSSIBILITIES AND APPROACHES OF TEACHING OF HISTORY OF RUSSIA TO UNIVERSITY STUDENTS (THROUGH THE EXAMPLE OF HISTORICAL MATERIALS ON THE AGRARIAN QUESTION AND OF THE RUSSIAN SOCIAL DEMOCRACY) - Sergei N. Folomeev (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes the college textbooks on the history of Russia on the specified theme, marks gaps and weaknesses in their content, searches for techniques of quality acquisition of the provided information. The subject of the study is to analyze the material of textbooks on the history of Russia and of the presentation of the policy of the Russian Social Democracy in late XIX-early XX century on the agrarian question. The purpose of the study is to optimize the methods of its presentation, identification and comprehensive assessment of the academic aspects of this topic, justifying their role and importance for the quality of learning. For a comprehensive and balanced study of the mentioned topics the author suggests to introduce to the students all the groups of recommended sources - the classics of Marxism, of the representatives of the Bolshevik and the Menshevik wings of the RSDLP, the program documents of the Russian and German Social Democrats on this issue, the views of K. Kautsky, the materials of the Zemstvo statistics, the position of the liberal populists, of modern scientific historical literature.